Correlation of gallium-68 prostate-specific membrane antigen positron emission tomography – Computed tomography/magnetic resonance imaging with histopathology characteristics in carcinoma prostate patients undergoing radical prostatectomy - P Taur Pratik; Deerush Kannan Sakthivel; S Tiwari Madhav; P Bafna Sandeep; Narasimhan Ragavan (Indian Journal of Urology)
Introduction: Gallium-68 prostate-specific membrane antigen positron emission tomography (68Ga-PSMA PET) is being increasingly used in patients with prostate cancer (PCa) for the staging and detection of lymph node (LN) metastases, despite a lack of prospective, validated evidence. We aimed to investigate the relationship between the PSMA PET findings (maximum standardized uptake [SUVmax] value) and the final histopathology results (Gleason Grade [GG], and LN positivity) in patients undergoing radical prostatectomy. Methods: This is a single centre, prospective, observational study of 63 consecutive eligible patients treated at a tertiary care centre in India. Patients underwent 68Ga-PSMA PET computed tomography with fusion magnetic resonance imaging for staging, followed by a Transrectal ultrasound guided prostate biopsy. All patients underwent robotic-assisted radical prostatectomy with extended pelvic LN dissection as per the standard protocol. Clinical parameters and SUVmax values were collected and analysed. Results: The median preoperative prostate specific antigen (PSA) was 15.0 ng/ml (interquartile range: 9.4–28.0). A statistically significant correlation was observed between the PSA values and the SUVmax uptake (P < 0.001). Additionally, there was a statistically significant correlation between the SUVmax of the prostatic lesion and the GG on the radical prostatectomy specimens (P = 0.025), and SUVmax of LN and LN involvement (P < 0.001). The sensitivity and specificity of the 68Ga-PSMA PET scan were 77.8% and 88.7%, respectively. Conclusions: SUVmax of the PCa lesion and the GG Group on the final histopathology correlates significantly. There is an increased SUV uptake in Gleason’s Score (GS) 8, 9 tumours as compared to GS 6 and 7.